2022
DOI: 10.1007/s12070-022-03310-y
|View full text |Cite|
|
Sign up to set email alerts
|

Parent’s Perspective on Teletherapy of Pediatric Population with Speech and Language Disorder During Covid-19 Lockdown in India

Abstract: Aim : The pandemic COVID-19 led to the sudden imposition of lockdown and travel restrictions worldwide, that made tele practice one of the most viable options for various hospitals and healthcare centres. The present study aimed at exploring the parental perspective on teletherapy, for children having speech and language delay, during the covid-19 pandemic lockdown. Material & method : A total of 100 parents with children with speech and language delays and who have undergone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…In a study it was found that majority of the patients partially trusted the therapist in audio-video communication (19). These results are found to be similar with another study (32), where majority of the felt that tele-therapy was convenient, costeffective and improved the attendance of the sessions. But some had reported about the increased use of gadgets and screen time for their children.…”
Section: Discussionsupporting
confidence: 67%
“…In a study it was found that majority of the patients partially trusted the therapist in audio-video communication (19). These results are found to be similar with another study (32), where majority of the felt that tele-therapy was convenient, costeffective and improved the attendance of the sessions. But some had reported about the increased use of gadgets and screen time for their children.…”
Section: Discussionsupporting
confidence: 67%
“…This phenomenon corresponded to the previous studies. Caregivers' self-assurance in evaluating uncertain symptoms increased during (asynchronous) telemedicine sessions, which helped them gauge the severity of their children's sickness and establish whether they need further expert treatment or not (Langkamp et al, 2015), and feeling highly motivated '' (Sikka, 2023). Because of this, they now understand their issues better, are less anxious, and feel more accepted (Saptandari et al, 2022).…”
Section: The Stronger Bond Between Caregivers and Childrenmentioning
confidence: 99%
“…Both patients and therapists' experiences were consistent with past studies. By providing accessible therapeutic alternatives to patients in remote areas, teletherapy helped cut expenses and staff shortages (Kotera et al, 2021;Stoll et al, 2020), thus making it more economical than in-person sessions (Sikka, 2023).…”
Section: Efficiencymentioning
confidence: 99%